Substrate arrays of iridium oxide microelectrodes for in vitro neuronal interfacing - Gawad, Shady; Giugliano, Michele; Heuschkel, Marc O.; Wessling, Boerge; Markram, Henry; Schnakenberg, Uwe; Renaud, Philippe; Morgan, Hywel (Frontiers in Neuroengineering, 2009)
The design of novel bidirectional interfaces for in vivo and in vitro nervous systems is an important step towards future functional neuroprosthetics. Small electrodes, structures and devices are necessary to achieve high-resolution and target-selectivity during stimulation and recording of neuronal networks, while significant charge transfer and large signal-to-noise ratio are required for accurate time resolution. In addition, the physical properties of the interface should remain stable across time, especially when chronic in vivo applications or in vitro long-term studies are considered, unless a procedure to actively compensate for degradation is provided. In this short report, we describe the use and fabrication of arrays of 120 planar microelectrodes (MEAs) of sputtered Iridium Oxide (IrOx). The effective surface area of individual microelectrodes is significantly increased using electrochemical activation, a procedure that may also be employed to restore the properties of the electrodes as required. The electrode activation results in a very low interface impedance, especially in the lower frequency domain, which was characterized by impedance spectroscopy. The increase in the roughness of the microelectrodes surface was imaged using digital holographic microscopy and electron microscopy. Aging of the activated electrodes was also investigated, comparing storage in saline with storage in air. Demonstration of concept was achieved by recording multiple single-unit spike activity in acute brain slice preparations of rat neocortex. Data suggests that extracellular recording of action potentials can be achieved with planar IrOx MEAs with good signal-to-noise ratios.